Cerceau et petite balle : les bienfaits des jeux pour la santé - Antoine Pietrobelli (Pallas, 2020)
Hoop and small ball are both games and sports that have a Greek origin, but were still practiced in the Graeco-Roman empire. Antyllus, a Pneumatist physician of the imperial age whose texts were preserved by Oribasius in his Medical Collections, devoted one chapter on each game in his book On remedies. These passages, relatively unknown and unexploited, give the point of view of a physician on these sports. As far as the hoop is concerned, Antyllus’ testimony can be compared with iconographic documents which pictured the hoop game. For the ball game, the chapter of the Pneumatist physician can be considered in the light of a contemporary treatise by Galen, The exercise with the small ball. By studying Antyllus’ chapters together with these other evidence, the historical and sociological background of both sport activities can be pointed out as well as the rules of these forgotten games. This paper also aims to show the medical values and the benefits on both body and mind attributed by the physicians to these activities.